Assessment of sociodemographic characteristics in a sample of breast cancer patients in Baghdad. - Al-Fadhli, Usama M.; Al-Shawi, Ameel F.; Al-Nuaimi, Ahmed S. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: In Iraq, breast cancer is the most common type of malignancy among the Iraqi population in general. It accounts for approximately one third of the registered female cancers according to the latest Iraqi Cancer Registry. Objectives: This study was conducted to assess the sociodemographic characteristics of patients with breast cancer in Baghdad. Methodology: This cross sectional study that was conducted in Baghdad City during a three months period from January to March 2016. It was conducted at Al-Amal National Hospital for Cancer Management. The questionnaire form gathered info about sociodemographic characteristics including: age, gender, educational attainment, marital status, living arrangement, finical status, and disease associated factors like disease duration and treatment modalities. Results: A random sample of 250 female patients with breast cancer was analyzed. The mean age was 56 years. The high frequency of breast cancer was among women aged 50-59 years, which is consistent with what was reported in the literature as age is one of the risk factors for developing breast cancer. The highest proportion of study sample completed their secondary school and about one fifth had university education. Married females constituted a large proportion of the study sample. In addition, parous women were frequent in the study sample, which was also consistent with global prevalence data of breast cancer. Conclusions: A high proportion of BC patients were married, multiparous, urban residence, and at least completed their secondary school.